2017
DOI: 10.1016/j.jacbts.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Precision Cardiology Through Multiscale Biology and Systems Medicine

Abstract: SummaryThe traditional paradigm of cardiovascular disease research derives insight from large-scale, broadly inclusive clinical studies of well-characterized pathologies. These insights are then put into practice according to standardized clinical guidelines. However, stagnation in the development of new cardiovascular therapies and variability in therapeutic response implies that this paradigm is insufficient for reducing the cardiovascular disease burden. In this state-of-the-art review, we examine 3 interco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 153 publications
(167 reference statements)
0
40
0
2
Order By: Relevance
“…There are already several large-scale biobanks and population-based cohorts including the UK Biobank (500,000 participants), the All of Us initiative (1000,000+ participants), and the Million Veterans Program, now include linkage to EHRs [73]. Deep phenotyping by way of using EHR-linked biobank data has been used as a resource for the discovery of novel drug targets [74][75][76][77]. For example, Dewey et al [78] used the exome sequencing data linked to the EHR from 58,000 patients collected at the Geisinger Health System and found that loss-of-function mutations in ANGPTL3 were correlated with the development of coronary artery disease.…”
Section: Suggestions To Improve Translational Researchmentioning
confidence: 99%
“…There are already several large-scale biobanks and population-based cohorts including the UK Biobank (500,000 participants), the All of Us initiative (1000,000+ participants), and the Million Veterans Program, now include linkage to EHRs [73]. Deep phenotyping by way of using EHR-linked biobank data has been used as a resource for the discovery of novel drug targets [74][75][76][77]. For example, Dewey et al [78] used the exome sequencing data linked to the EHR from 58,000 patients collected at the Geisinger Health System and found that loss-of-function mutations in ANGPTL3 were correlated with the development of coronary artery disease.…”
Section: Suggestions To Improve Translational Researchmentioning
confidence: 99%
“…The same machine learning algorithms have been used widely in both pharmaceutical and toxicological research 30 (Table 1). Statistical machine learning methods have also been used to interrogate, model, and learn from complex multi-omics data to help to address uncertainties about the connections between different types of data 39 . For example, machine learning methods have been applied to electronic health records to accurately predict multiple medical events from different centers without site-specific data harmonization, with recent data suggesting that deep learning was comparable to regularized logistic regression in this case 40 .…”
Section: Machine Learning Models In Actionmentioning
confidence: 99%
“…173,174 Similarly, but at the level of whole physiological systems or organs, one can turn to models of the heart, 164 of the liver, 175 and of the skeletal system 176 as valid examples of multiscale systems. Further examples include multiscale modeling approaches aiming at predicting tumor evolution, 177 the modeling of angiogenesis, 178 studying the signaling pathways that are relevant for specific kinds of cancer, 74 predicting cardiotoxicity, 179 and introducing so-called precision cardiology, 180 just to name a few examples. Also, the reader is referred to the numerous pertinent review articles (see, for instance, Refs.…”
Section: Limitations Of Modeling Approaches At Different Biological Smentioning
confidence: 99%